COMPARISION OF BLOOD PRESSURE STABILIZATION BETWEEN 6% HYDROXYETHYL STARCH 130/0.4 WITH NATRICLORUA 0,9% BEFORE EPIDURAL ANESTHESIA IN CEASAREAN SECTION (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate effect of blood pressure stabilization between 6% Hydroxyethyl starch 130/0.4 with Natriclorua 0.9% IV before epidural anesthesia in C-section.Methodology: This is a single blind, randomized control trial among singleton pregnant women in Department of Surgery and Anesthesia, National hospital of Obtetrics and Gynecology from May 2020 to November 2020.Results: Mean period of pre-anesthesia T10 in group 1 was 2,88 ± 0,43 vs 2,85 ± 0,70 in group 2 (p>0,05). Mean period of pre-anesthesia T10 in group 1 was 4,04 ± 0,57 vs 3,80 ± 0,72 in group 2 (p>0,05). The rate of insensitivity in both group was 100%. Value of systolic, diastolic and mean of blood pressure was elevated compare to those before infusion (p
Keywords: 6% Hydroxyethyl starch 130/0.4, Natriclorua 0,9%, epidural anesthesia, C-section.